La publicidad en la contratación estatal : una mirada a las ventajas e inconsistencias del Sistema Electrónico de Contratación Estatal - SECOP (2019)
This article identifies the practical difficulties of public servants in complying with the principle of publicity within the contractual process, in accordance with public policies issued by the public procurement agency Colombia Compra Eficiente, the precepts of the General Statute of Contracting of Public Administration and its regulatory decrees. In order to carry out the proposed work, the constitutional norms, the pronouncements of the Constitutional Court, the progress and normative evolution of the advertising principle in the state contracting are reviewed. Specifically, the way to guarantee this principle and the responsibilities of public servants is verified, under traditional contractual practice and online contracting, making use of information technologies with the use of the SECOP II platform. In addition, the practices adopted by officials to avoid non-compliance with the principle of publicity when the causes are different to them are identified. Finally, some recommendations or challenges are established to eradicate the causes that affect the principle of publicity, promote morality and transparency in contracting.